Nutritional profile of ultra-processed foods consumed by children in Rio de Janeiro - Carine de Oliveira Avelar Anastácio; Juliana Martins Oliveira; Milena Miranda de Moraes; Jorginete de Jesus Damião; Inês Rugani Ribeiro de Castro (Universidade de São Paulo, 2020)
ABSTRACT OBJECTIVE To analyze the nutritional composition of ultra-processed foods consumed by children that attend basic health units. METHODS This is a cross-sectional study with a representative probabilistic sample of 536 children aged between 6 and 59 months treated at a health unit in the city of Rio de Janeiro. Nutritional information was extracted from labels of the ultra-processed foods referred to in a 24-hour recall. The 351 foods mentioned were divided into 22 groups and 38 subgroups according to the type of product, and they were characterized according to the averages of the values for energy, total fats, saturated fats, trans fats and sodium in 100 grams of the product, in addition to presence, number, and type of "other sweeteners". The nutritional Profile Model of the Pan American Health Organization was applied for each food and for the average of nutrient content obtained for each group to examine the occurrence of critical nutrients excess. RESULTS Ultra-processed foods contained high energy value and high levels of total fats, saturated fats, trans fats, and sodium. Out of the total of ultra-processed foods, 66% presented excess of at least one critical nutrient, with emphasis on requeijões and ultra-processed cheeses, instant noodles, and industrialized and sausage-like meats, which presented 100% of foods with excess of total fats, saturated fats and sodium. Out of the 21 groups, the following exceeded the limit established by the Pan American Health Organization: for total fats, 10 groups; for saturated fats, 11; for trans fats, 3; and sodium, 13. Requeijões and ultra-processed cheeses; industrialized and sausage-like meats; and biscuits exceeded this limit in all parameters. Out of the set of ultra-processed foods analyzed, 13.4% contained "other sweeteners" (eight different types). CONCLUSIONS The ultra-processed foods analyzed presented unbalanced nutritional profile, and two thirds presented excess of at least one critical nutrient. Educational actions and regulatory measures are necessary to better inform the population and to discourage its consumption.